430 OSELTAMIVIR PROPHYLAXIIS IN HEMATOPOIETIC STEM CELL TRANSPLANTATION RECIPIENTS: A CASE-CONTROL STUDY. Issue 1 (1st January 2007) - Vu, D.; Peck, A.; Nichols, G.; Varley, C.; Englund, J.; Corey, L.; Boeckh, M.
Abstract : Background: Oseltamivir is safe and effective in immunocompetent persons, and prophylactic use is recommended in the setting of an influenza outbreak; however, no data exist for use as prophylaxis among hematopoietic stem cell transplantation (HCT) candidates and recipients. Methods: In January 2002, an influenza outbreak was identified when four cases occurred within 1 week at an outpatient residential facility for HCT patients. Oseltamivir prophylaxis (75 mg QD) was initiated 1 week after and given to 44 patients living in the same housing facility (25 post-HCT recipients, 19 pre-HCT candidates). Retrospectively, these 44 patients were matched 1:1 with controls transplanted between 1994 and 2003 who did not receive prophylaxis according to donor type, conditioning regimen, CMV serostatus, and recipient age ± 5 years. Frequency of clinical and laboratory adverse events (AEs) was determined by chart review and graded using the NCI Common Toxicity Criteria (CTC), grades ranging from 0 (no AE) to 5 (death). Results: Forty-four patients received oseltamivir for a median of 24 days (range 15-88). Eleven pre-HCT candidates received HCT while taking prophylaxis and did not develop influenza. One of 44 patients developed influenza infection 28 days after oseltamivir was initiated; this patient had been noncompliant with dosing. No CTC grade 5 AEs occurred in either the prophylaxis or control group. The proportion of clinical AEs meeting CTC grades 2 to 4 or 3 to 4 was not significantly different between patients receiving oseltamivir and controls. There was also no difference in the proportion of laboratory abnormalities meeting CTC grades 2 to 4 between groups. Conclusion: Oseltamivir prophylaxis appeared to be safe and well tolerated in managing an influenza outbreak in an HCT outpatient residential setting.